The EurMedStat proposals on indicators for price and utilisation (Italian Journal of Public Health, 2006)
Medicines account for an increasing proportion of healthcare budgets in all European countries. The EuroMedStat project aims to establish methods and systems for comparing the publicly funded pharmaceutical markets across Europe. A key issue is how to compare prices across countries. There are established methods for bilateral comparisons between two countries which are used in pricing negotiations but no means of a broader overview. Difficulties exist because of: a lack of directly comparable packages of individual medicines across Europe; currency conversion in some countries, despite the use of the euro; a range of different prices from different parts of the supply chain that could be studied; differences even within what are included in prices across countries (e.g. pharmacy fees etc); and most important, lack of availability of data on many of these points. Our aim was to produce pragmatic suggestions and these are presented. We suggest that the price used in the pharmacy retail price; that the denominator for price is the defined daily dose; and that the package size selected is that which most closely equates to one month’s treatment at the most commonly used dosage. From this, we derive a number of markers of the efficiency of national markets. It is important that the limitations of these are understood and that they are sued only as broad indicators to begin exploring areas of possible concern, and not for instance in price setting. These indicators now need field testing and the project will extent to include the new accession countries.
Keywords: Medicines; prices; utilisation; methods